2013
DOI: 10.1016/j.kjms.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse malignant peritoneal mesothelioma

Abstract: Mesothelioma often originates in the pleura and less frequently in the peritoneum. This article describes a rare case of diffuse malignant peritoneal mesothelioma in a 54-year-old male construction worker who was admitted to our hospital with a 2-month history of progressive abdominal distention. Abdominal computed tomography revealed extensive peritoneal nodularity and omental cake along with massive ascites. Imaging findings initially suggested peritoneal carcinomatosis, primary peritoneal carcinoma, and tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…This patient was a bus driver and had no history of asbestos exposure, which is the most common cause of malignant mesothelioma, particularly in men, possibly because of occupational risks (3,18,19). Asbestos exposure is evident in 80% of malignant pleural mesothelioma cases but in only 33% to 50% of MPM cases.…”
Section: Discussionmentioning
confidence: 95%
“…This patient was a bus driver and had no history of asbestos exposure, which is the most common cause of malignant mesothelioma, particularly in men, possibly because of occupational risks (3,18,19). Asbestos exposure is evident in 80% of malignant pleural mesothelioma cases but in only 33% to 50% of MPM cases.…”
Section: Discussionmentioning
confidence: 95%
“…There are several different histological types of malignant peritoneal mesothelioma: epithelioid, sarcomatous/fibrous, and biphasic [ 6 ]. Epithelioid type is the most common presentation, followed by biphasic and sarcomatoid types.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratin staining is used to confirm invasion and to distinguish malignant mesothelioma from sarcoma or melanoma [ 10 ]. Malignant mesothelioma is further differentiated from adenocarcinoma by the use of specific markers: calretinin, WT1, cytokeratin 5/6, epithelial membrane antigen (EMA), mesothelin, and anti-mesothelial cell antibody [ 6 , 10 ]. In addition to the positive staining for the aforementioned markers, the absence of staining for antigens such as carcinoembryonic antigen (CEA), thyroid transcription factor-1, tumor glycoproteins MOC-31, B72.3 and Ber-EP4, and epithelial glycoprotein BG8 is necessary for definitive diagnosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most peritoneal mesotheliomas are epithelial and are histologically similar to pleural mesothelioma; peritoneal mesotheliomas have a tubulopapillary pattern and are stromal malignant [27]. As characterized by Shih CA et al [31] in describing a case in a 54 old male construction worker "…diffuse malignant peritoneal mesothelioma is a rare disease characterized by a difficult diagnosis, different presentations, variable course, and poor prognosis. " In a study of 25 female patients [32], survival prognosis was found to be from 1 month to 15 years, often less than one year.…”
Section: Introductionmentioning
confidence: 99%